The protective effects of whortleberry extract against cisplatin-induced ototoxicity in rats - Doğukan Özdemir; Abdulkadir Özgür; Yıldıray Kalkan; Suat Terzi; Levent Tümkaya; Adnan Yılmaz; Metin Çeliker; Engin Dursun (Brazilian Journal of Otorhinolaryngology, 2019)
Introduction: Cisplatin is one of the main chemotherapeutic agents used for the treatment of many types of cancer. However, ototoxicity, one of the most serious side effects of cisplatin, restricts its usage. Objective: We aimed to investigate the protective effects of whortleberry extract against cisplatin-induced ototoxicity by evaluating hearing and histopathological cochlear damage and by measuring the biochemical parameters affected byoxidative stress. Methods: Forty-eight male rats were included in the study after performing Distortion Product Otoacoustic Emission test to confirm that their hearing levels were normal. The rats were randomly divided into six groups: the control group, the sham group, and, which received only whortleberry extract, only cisplatin, cisplatin + 100 mg whortleberry extract, cisplatin + 200 mg whortleberry extract, respectively. Audiologic investigation was performed by performing the Distortion Product Otoacoustic Emission test at the beginning and at the eighth day of the study. Cardiac blood samples were collected for biochemical analysis, and the rats were sacrificed to obtain cochlear histopathological specimens on the eighth day. Results: The results revealed that whortleberry protects hearing against cisplatin-induced ototoxicity independent of the dose. However, high doses of whortleberry extract are needed to prevent histopathological degeneration and oxidative stress. Conclusion: The results obtained in this study show that whortleberry extract has a protective effect against cisplatin-induced ototoxicity. Resumo: Introdução: A cisplatina é um dos principais agentes quimioterápicos utilizados para o tratamento de muitos tipos de câncer. No entanto, a ototoxicidade, um dos efeitos colaterais mais graves da cisplatina, restringe seu uso. Objetivo: Nosso objetivo foi investigar os efeitos protetores do extrato de uva-do-monte contra a ototoxicidade induzida por cisplatina, avaliar o dano auditivo e histopatológico coclear e medir os parâmetros bioquímicos afetados pelo estresse oxidativo. Método: Foram incluídos no estudo 48 ratos machos após teste de emissão otoacústica evocada por produto de distorção para confirmar que seus níveis de audição eram normais. Os ratos foram divididos aleatoriamente em seis grupos: o grupo controle, o grupo simulado, o que recebeu apenas extrato de uva-do-monte, o que recebeu apenas cisplatina, o que recebeu cisplatina + 100 mg de extrato de uva-do-monte e o que recebeu cisplatina + 200 mg de extrato de uva-do-monte, respectivamente. A investigação audiológica foi feita através do teste de emissão otoacústica de produto de distorção no início e no oitavo dia do estudo. As amostras de sangue cardíaco foram coletadas para análise bioquímica e os ratos foram sacrificados para obtenção de espécimes histopatológicos cocleares no oitavo dia. Resultados: Os resultados revelaram que o extrato de uva-do-monte protege a audição contra a ototoxicidade induzida por cisplatina, independentemente da dose. No entanto, são necessárias doses elevadas do extrato para evitar a degeneração histopatológica e o estresse oxidativo. Conclusão: Os resultados obtidos neste estudo mostram que o extrato de uva-do-monte tem um efeito protetor contra a ototoxicidade induzida por cisplatina. Keywords: Ototoxicity, Cisplatin, Whorleberry extract, Palavras-chave: Ototoxicidade, Cisplatina, Extrato de uva-do-monte